PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN (Studi Pada Perusahaan Real Estate & Property yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2013) - Alyda Noor Prantama (Jurnal Administrasi Bisnis, 2015)
"> This Research aims to: determine the effect of good corporate governance against financial performance. Thisresearch uses quantitative research. This study uses secondary data from Indonesian Capital Market Directory(ICMD) and IDX, a summary of the company’s performance and financial reports obtained from BEI. Thesample selection is done by purposive sampling method. Data analysis using the classical assumption test andmultiple linear regression. Indicators of good corporate governance in this study is institutional ownership, andthe proportion of independent directors. Financial performance indicators, namely ROA and ROE. The studypopulation was a company listed on the Indonesian Stock Exchange in 2011-2013.Keyword : corporate governance, institutional ownership, proportion of independent directors, financialperformance, ROA and ROE.